Possibilities of using and recovery of wastes after mining and preparation of iron ores from dumps in Częstochowa Ore-bearing Basin - Gawor, Łukasz; Warcholik, Witold; Dolnicki, Piotr (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
The paper presents a cataloguing process and characteristic of dumping grounds after exploitation and preparation of iron ores in the region of Czestochowa. Dogger siderite ores in the Czestochowa region have been exploited for over 600 years. The first mine was closed in 1970 in Rudniki, in the neighbourhood of Zawiercie, the last closed mine was „Wręczyca” in Wręczyca Wielka. In the region of Czestochowa a cataloguing and description of 41 dumping grounds was done, based on literature study. These objects are situated between following towns: Konopiska, Kłobuck and Zawiercie. Conducted field works led to the valorisation of the dumps concerning possibility of iron-bearing materials recovery from wastes disposed on the ground surface. In the case of potential possibilities of recovery of iron form waste material it is estimated that a total mass of siderite included in wastes is 5.8 million Mg. The directions of reclamation and using of the chosen objects are proposed.